Negative electrode active material layer, battery, and method for producing negative electrode active material layer
By using a carbon-based negative electrode active material with a specific range of adhesive content and coating ratio in the negative electrode active material layer of the battery, combined with the dry-type manufacturing method, the problems of improved battery discharge capacity and resistance are solved, and more efficient battery performance is achieved.
Patent Information
- Application Number
- CN202410432155.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-22
- Filing Date
- 2024-04-11
- Publication Date
- 2025-02-25
AI Technical Summary
The battery containing the electrode active material layer made by the dry process has room for improvement in discharge capacity and resistance.
A negative electrode active material layer is used, including a carbon-based negative electrode active material and a coated adhesive, the content of the adhesive is 4.0 to 9.0 mass%, and the coating ratio of the negative electrode active material produced by the adhesive is 8.0 to 25%. This layer is formed on the substrate by a dry process.
The discharge capacity and resistance of the battery are improved, and by optimizing the content and coating ratio of the adhesive, the increase of irreversible capacity and the increase of the contact resistance between the negative electrode active substances are suppressed.
Smart Images

Figure BDA0004785974990000131
Abstract
Description
Technical Field
[0001] The present disclosure relates to a negative electrode active material layer, a battery, and a method for manufacturing the negative electrode active material layer. Background Art
[0002] A lithium-ion secondary battery typically has an electrode active material layer containing an electrode active material on a current collector. By forming the electrode active material layer homogeneously, the performance of the battery using the electrode active material layer can be stabilized. Generally, a slurry-like electrode material obtained by dispersing the electrode active material in a liquid medium is supplied to the current collector, and after drying, compaction is performed to manufacture the electrode active material layer. On the other hand, it is also known that the following method for manufacturing an electrode active material layer (dry method) is performed without using a liquid medium, thereby omitting the drying process, saving energy and manufacturing at low cost.
[0003] For example, Japanese Patent Application Laid-Open No. 2023-016208 discloses a method for manufacturing an electrode comprising the following steps (a) to (f). (a) Preparing particles comprising an active material powder and a binder. (b) Supplying the particles to the surface of a roller. (c) Charging the particles. (d) Transporting the particles from a first region to a second region by rotating the roller. (e) Forming a first electric field between the second region and the third region so that the particles fly from the second region to the third region. (f) Forming a second electric field between the third region and a substrate so that the particles fly from the third region to the substrate. In this manufacturing method, in the vertical direction, the second region is located at a position lower than the first region. In a direction intersecting the vertical direction, the third region is separated from the second region. In the vertical direction, the substrate is located at a position lower than the third region. Moreover, an active material layer is formed by attaching the particles to the substrate. According to the method for manufacturing an electrode of Japanese Patent Application Laid-Open No. 2023-016208, uneven coating can be reduced. Summary of the invention
[0004] The dry process (dry method) omits the drying step and can produce the electrode active material layer in an energy-saving and low-cost manner. However, the discharge capacity and resistance of the battery including the electrode active material layer produced by the dry process still have room for improvement.
[0005] Therefore, an object of the present disclosure is to provide a negative electrode active material layer capable of improving the discharge capacity and resistance of a battery.
[0006] The present disclosure adopts the following means to achieve the above-mentioned objectives.
[0007] Solution 1
[0008] A negative electrode active material layer for a battery, wherein the negative electrode active material layer comprises a carbon-based negative electrode active material and a binder for coating the carbon-based negative electrode active material, the binder content is 4.0 to 9.0% by mass relative to the total amount of the negative electrode active material layer, and the coverage of the negative electrode active material produced by the binder is 8.0 to 25%.
[0009] Solution 2
[0010] The negative electrode active material layer according to claim 1, wherein the content of the binder is 6.0 to 9.0 mass % based on the total amount of the negative electrode active material layer.
[0011] Solution 3
[0012] The negative electrode active material layer according to claim 1, wherein the content of the binder is 7.0 to 8.0 mass % based on the total amount of the negative electrode active material layer.
[0013] Solution 4
[0014] The negative electrode active material layer according to any one of aspects 1 to 3, wherein the binder is polyvinylidene fluoride.
[0015] Solution 5
[0016] A battery comprising the negative electrode active material layer according to any one of aspects 1 to 4.
[0017] Solution 6
[0018] A method for manufacturing a negative electrode active material layer according to any one of Schemes 1 to 4, comprising: mixing a carbon-based negative electrode active material and a binder in an amount of 4.0 to 9.0 mass % relative to the total amount of the negative electrode active material layer to prepare a negative electrode composite; and coating the negative electrode composite on a substrate using a dry method to form the negative electrode active material layer.
[0019] Solution 7
[0020] The manufacturing method according to Scheme 6, wherein the dry process is electrostatic painting.
[0021] Solution 8
[0022] The production method according to aspect 6 or 7, wherein the average particle size of the carbon-based negative electrode active material is 5 to 30 μm, and the average particle size of the binder is 100 nm to 500 nm.
[0023] According to the negative electrode active material layer of the present disclosure, the discharge capacity and resistance of the battery can be improved. DETAILED DESCRIPTION
[0024] The following describes the embodiments of the present disclosure in detail. The present disclosure is not limited to the following embodiments, and various modifications can be made within the scope of the gist of the present disclosure.
[0025] In the present disclosure, "composite material" refers to a composition that can directly constitute a negative electrode (positive electrode) active material layer, or a composition that also contains other components to constitute a negative electrode (positive electrode) active material layer. In addition, in the present disclosure, "composite material slurry" refers to a slurry that contains a dispersion medium in addition to the "composite material" and is applied and dried to form a negative electrode (positive electrode) active material layer.
[0026] Negative electrode active material layer
[0027] In the negative electrode active material layer for the battery disclosed herein, the negative electrode active material layer comprises a carbon-based negative electrode active material and a binder for coating the carbon-based negative electrode active material. The content of the binder is 4.0 to 9.0% by mass relative to the total amount of the negative electrode active material layer, and the coverage rate of the negative electrode active material produced by the binder is 8.0 to 25%.
[0028] According to the negative electrode active material layer of the present disclosure, the discharge capacity and resistance of the battery can be improved.
[0029] The negative electrode active material layer for the battery disclosed in the present invention comprises a carbon-based negative electrode active material and a binder for coating the carbon-based negative electrode active material. The inventors have conducted research and found that when the amount of the binder and the coating rate of the negative electrode active material by the binder are within a specific range, the discharge capacity and resistance of the battery are improved.
[0030] The details of the mechanism for improving the discharge capacity and resistance of the battery are not clear, but it is speculated to be based on the following mechanism. In general, it is known that a film (Solid Electrolyte Interphase (SEI)) is formed on the surface of the negative electrode active material during the charge and discharge of the battery. Solid Electrolyte Interphase is hereinafter referred to as SEI. It is believed that by making the amount of binder in the negative electrode active material layer more than 4%, the surface of the negative electrode active material is partially covered with the binder using the binder, thereby suppressing the formation of SEI, thereby suppressing the increase in irreversible capacity. On the other hand, it is believed that by making the amount of binder less than 9% and making the coverage of the negative electrode active material by the binder 8.0 to 25%, the surface of the negative electrode active material is prevented from being excessively covered with the binder, thereby suppressing the increase in contact resistance between the negative electrode active materials.
[0031] Composition of negative electrode active material layer
[0032] The negative electrode active material layer includes a carbon-based negative electrode active material and a binder that covers the carbon-based negative electrode active material.
[0033] The negative electrode active material layer may optionally contain a conductive auxiliary agent and a solid electrolyte.
[0034] Carbon-based negative electrode active material
[0035] There is no particular limitation on the carbon-based negative electrode active material. The carbon-based negative electrode active material may be a carbon material that can absorb and release metal ions such as lithium ions. There is no particular limitation on the carbon material. Examples of the carbon material include hard carbon, soft carbon, and graphite.
[0036] There is no particular limitation on the average particle size of the carbon-based negative electrode active material. However, from the viewpoint of obtaining a negative electrode active material layer with high discharge capacity and low resistance, the average particle size of the carbon-based negative electrode active material is preferably 5 to 30 μm. In addition, the average particle size of the carbon-based negative electrode active material may be greater than 5 μm, greater than 7 μm, greater than 9 μm, greater than 11 μm, greater than 13 μm, or greater than 15 μm. In addition, the average particle size of the carbon-based negative electrode active material may be less than 30 μm, less than 28 μm, less than 26 μm, less than 24 μm, less than 22 μm, or less than 20 μm. Among them, the average particle size can be obtained by observation using a scanning electron microscope (SEM).
[0037] Adhesives
[0038] As adhesive, it is not particularly limited. For example, the adhesive can be a material such as polyvinylidene fluoride (PVdF), butadiene rubber (BR), polytetrafluoroethylene (PTFE) or styrene butadiene rubber (SBR), or a combination thereof, but is not limited to these. The adhesive is not particularly limited. However, from the viewpoint of redox resistance and adhesion, the adhesive is preferably polyvinylidene fluoride and polytetrafluoroethylene, more preferably polyvinylidene fluoride.
[0039] The average particle size of the binder is not particularly limited, and may be 100 nm to 500 nm. In addition, the average particle size of the binder may be 100 nm or more, 120 nm or more, or 140 nm or more, and may be 500 nm or less, 450 nm or less, 400 nm or less, 350 nm or less, 300 nm or less, or 250 nm or less. The average particle size may be determined by observation using a scanning electron microscope (SEM).
[0040] Conductive additives
[0041] There is no particular limitation on the conductive additive. For example, the conductive additive may be vapor grown carbon fiber (VGCF), acetylene black (AB), Ketjen black (KB), carbon nanotube (CNT), carbon nanofiber (CNF), etc. However, the conductive additive is not limited to these.
[0042] Solid electrolyte
[0043] The material of the solid electrolyte is not particularly limited, and for example, the solid electrolyte may be a sulfide solid electrolyte, an oxide solid electrolyte, or a polymer electrolyte, etc. However, the material of the solid electrolyte is not limited thereto.
[0044] Examples of sulfide solid electrolytes include sulfide amorphous solid electrolytes, sulfide crystalline solid electrolytes, and argyrodite solid electrolytes, but are not limited to these. Specific examples of sulfide solid electrolytes include Li2S-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-P2S5-GeS2, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li 7-x PS 6-x Cl x Or, as specific examples of sulfide solid electrolytes, their combinations can be listed. However, sulfide solid electrolytes are not limited to these. Li2S-P2S5 is Li7P3S 11 , Li3PS4, Li8P2S9, etc. Li2S-P2S5-GeS2 is Li 13 GeP3S 16 , Li 10 GeP2S 12 wait.
[0045] Examples of oxide solid electrolytes include Li7La3Zr2O 12 , Li 7-x Ln3Z 1-x Nb x O 12 , Li 7- 3x La3Zr2Al x O 12 , Li 3x La 2 / 3-x TiO3、Li 1+x Al x Ti 2-x (PO4)3、Li 1+x Alx Ge 2-x (PO4)3, Li3PO4, or Li 3+x PO 4- x N x (LiPON), etc. However, the oxide solid electrolyte is not limited to these.
[0046] The sulfide solid electrolyte and the oxide solid electrolyte may be glass or crystallized glass (glass ceramic).
[0047] Examples of the polymer electrolyte include polyethylene oxide (PEO), polypropylene oxide (PPO), and copolymers thereof, but the polymer electrolyte is not limited to these.
[0048] Negative electrode collector layer
[0049] The negative electrode active material layer can be formed on the negative electrode collector layer. There is no particular limitation on the material used for the negative electrode collector layer. However, as the material for the negative electrode collector layer, a material that can be used as a negative electrode collector of a battery can be appropriately adopted. The material for the negative electrode collector layer can be, for example, copper, copper alloy, stainless steel (SUS), nickel, and products of plating, coating or evaporating nickel, chromium, carbon, etc. on these metals. However, the material for the negative electrode collector layer is not limited to these.
[0050] The content of binder in the negative electrode active material layer
[0051] The content of the binder in the negative electrode active material layer is 4.0 to 9.0 mass % relative to the total amount of the negative electrode active material layer.
[0052] The content of the binder in the negative electrode active material layer is not particularly limited, but is preferably 6.0 to 9.0 mass %, more preferably 7.0 to 8.0 mass %, relative to the total amount of the negative electrode active material layer from the viewpoint of improving discharge capacity and resistance.
[0053] The content of the binder in the negative electrode active material layer may be 4.0% by mass or more, 4.5% by mass or more, 5.0% by mass or more, 5.5% by mass or more, 6.0% by mass or more, 6.5% by mass or more, or 7.0% by mass or more. In addition, the content of the binder in the negative electrode active material layer may be 9.0% by mass or less, 8.5% by mass or less, or 8.0% by mass or less.
[0054] Coverage of negative electrode active material by binder
[0055] The coverage of the negative electrode active material by the binder is 8.0 to 25%.
[0056] From the perspective of improving discharge capacity and resistance, the coverage of the negative electrode active material produced by the binder can be greater than 8.0%, greater than 10%, greater than 12%, greater than 14%, greater than 16%, or greater than 18%, and can be less than 25%, less than 23%, or less than 21%.
[0057] The coating of the negative electrode active material by the binder refers to a state where the binder is arranged on the surface of the negative electrode active material (the binder exists on the surface of the negative electrode active material), typically indicating that the binder exists in an attached or bonded state, and a part of the binder may be contained in the interior of the negative electrode active material.
[0058] The coverage of the negative electrode active material by the binder can be determined by energy dispersive X-ray spectroscopy (EDX). Specifically, a scanning electron microscope (SEM) is used to observe the side of the negative electrode active material layer, and then EDX is used to map the elements contained only in the binder. For example, when PVdF is used as the binder, fluorine atoms are mapped. The mapped image data is binarized to calculate the area of the binder and the negative electrode active material. The coverage of the negative electrode active material by the binder (%) can be calculated as the ratio of the area of the binder to the area of the negative electrode active material.
[0059] Battery
[0060] The battery of the present disclosure includes the negative electrode active material layer of the present disclosure.
[0061] The battery disclosed herein may be a liquid battery containing an electrolyte as an electrolyte layer, or may be a solid battery having a solid electrolyte layer as an electrolyte layer. Furthermore, with respect to the present disclosure, a "solid battery" refers to a battery that uses at least a solid electrolyte as an electrolyte. Therefore, a solid battery may also use a combination of a solid electrolyte and a liquid electrolyte as an electrolyte. In addition, the battery disclosed herein may be an all-solid battery, that is, a battery that uses only a solid electrolyte as an electrolyte.
[0062] Liquid battery
[0063] When the battery of the present disclosure is a liquid-based battery, it may further include a positive electrode active material layer, an electrolytic solution as an electrolyte layer, and a separator (diaphragm) between the positive electrode active material layer and the negative electrode active material layer.
[0064] Positive electrode active material layer
[0065] The positive electrode active material layer may contain a binder, a conductive auxiliary agent, and a solid electrolyte as necessary in addition to the positive electrode active material.
[0066] There is no particular limitation on the material of the positive electrode active material. For example, the positive electrode active material may be lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), nickel·cobalt·manganese oxide (NCM), LiCO 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, by Li 1+ x Mn 2-x-y M y O4 represents the composition of the heterogeneous elements replaced Li-Mn spinel, LiNi x Co y Al z O2 (NCA), etc. However, the positive electrode active material is not limited to these. 1+x Mn 2-x-y M y In the heterogeneous element substituted Li—Mn spinel having a composition represented by O4, M is one or more metal elements selected from the group consisting of Al, Mg, Co, Fe, Ni and Zn.
[0067] For the binder, the conductive additive, and the solid electrolyte, reference can be made to the description of the above-mentioned “Configuration of the Negative Electrode Active Material Layer”.
[0068] Positive electrode collector layer
[0069] The positive electrode active material layer can be formed on the positive electrode collector layer. There is no particular limitation on the material used for the positive electrode collector layer, and a material that can be used as a positive electrode collector of a battery can be appropriately used. For example, the material used for the positive electrode collector layer can be aluminum, stainless steel (SUS), chromium, gold, platinum, iron, titanium, zinc, etc., and products of plating, coating or evaporating nickel, chromium, carbon, etc. on these metals. However, the material used for the positive electrode collector layer is not limited to these.
[0070] Electrolyte
[0071] The electrolyte solution is not particularly limited, but preferably contains a supporting salt and a solvent.
[0072] As supporting salts (lithium salts) of electrolytes having lithium ion conductivity, inorganic lithium salts and organic lithium salts can be cited, for example. Examples of inorganic lithium salts include LiPF6, LiBF4, LiClO4, LiAsF6, etc. Examples of organic lithium salts include LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(FSO2)2, LiC(CF3SO2)3, etc.
[0073] The solvent used in the electrolytic solution is not particularly limited, and examples thereof include non-aqueous solvents and aqueous solvents.
[0074] As the non-aqueous solvent, for example, cyclic esters (cyclic carbonates) and chain esters (chain carbonates) can be listed. Examples of cyclic esters (cyclic carbonates) include ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC). Examples of chain esters (chain carbonates) include dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). The electrolyte can be used alone or in combination of two or more. The electrolyte preferably contains two or more solvents.
[0075] As the aqueous solvent, for example, an aqueous solvent containing water as a solvent can be listed, and in addition to water, a solvent other than water can be included. As the solvent other than water, for example, one or more organic solvents selected from ethers, carbonates, nitriles, alcohols, ketones, amines, amides, sulfur compounds and hydrocarbons can be listed.
[0076] Separator
[0077] The separator is not particularly limited, and for example, nonwoven fabrics of polyolefin, polyamide, polyimide, or the like can be used.
[0078] Solid-state batteries
[0079] When the battery of the present disclosure is a solid battery, it may further include a positive electrode active material layer and a solid electrolyte layer as an electrolyte layer.
[0080] The positive electrode active material layer may contain a binder, a conductive auxiliary agent, a solid electrolyte, etc., in addition to the positive electrode active material, as necessary. For details, see the description of "liquid system battery".
[0081] The solid electrolyte layer may contain a binder etc. as necessary in addition to the solid electrolyte. For the solid electrolyte and the binder, reference can be made to the description related to the above-mentioned "Configuration of the Negative Electrode Active Material Layer".
[0082] Method for manufacturing negative electrode active material layer disclosed herein
[0083] The negative electrode active material layer disclosed in the present invention can be manufactured by a method including the following steps: mixing a carbon-based negative electrode active material and a binder in an amount of 4.0 to 9.0 mass % relative to the total amount of the negative electrode active material layer to prepare a negative electrode composite; and coating the negative electrode composite on a substrate using a dry method to form the negative electrode active material layer.
[0084] According to the method for manufacturing a negative electrode active material layer disclosed in the present invention, a negative electrode active material layer that helps improve the discharge capacity and resistance of a battery can be obtained. Furthermore, in the method for manufacturing a negative electrode active material layer disclosed in the present invention, a negative electrode composite material can be arranged on a current collector in a powder state to manufacture a negative electrode active material layer. That is, a material that is different from the past and does not contain a solvent can be used, so the process of removing the solvent can be omitted.
[0085] Negative electrode composite
[0086] The negative electrode composite material comprises a carbon-based negative electrode active material and a binder. In addition, the negative electrode composite material may optionally contain a conductive auxiliary agent and a solid electrolyte.
[0087] The negative electrode composite material can be in a dry state or in a wet state. That is, the negative electrode composite material can contain a solvent (liquid). However, the negative electrode composite material is different from the negative electrode composite material slurry (particle dispersion). In the negative electrode composite material, the solvent forms droplets, and the solvent (liquid) is dispersed in the powder (solid). In the negative electrode composite material slurry, the solvent is the dispersion medium, and the powder (solid) is dispersed in the solvent (liquid).
[0088] The carbonaceous negative electrode active material and binder contained in the negative electrode composite can refer to the description of "Constitution of negative electrode active material layer". In addition, the content of the binder can refer to the description of "Content of binder in negative electrode active material layer".
[0089] For the conductive additive and solid electrolyte optionally contained in the negative electrode composite material, the description in “Configuration of the negative electrode active material layer” can be referred to.
[0090] The negative electrode composite material can be obtained by, for example, mixing a mixture containing a carbon-based negative electrode active material and a binder with a multi-purpose small mixer-pulverizer, but the present invention is not limited to this.
[0091] Dry method
[0092] The dry method is not particularly limited as long as it is a method of forming an electrode active material layer on a current collector using the above-mentioned negative electrode composite. The dry method is not particularly limited, and examples thereof include electrostatic coating, calendering film forming, and the like.
[0093] As electrostatic coating, for example, an electrostatic screen film forming method can be cited, but it is not limited to this case. Specifically, a high voltage is applied between the electrostatic screen and the collector to generate an electrostatic field between the electrostatic screen and the collector. On the electrostatic screen, when the charged electrode composite falls from the opening of the electrostatic screen into the electrostatic field, a Coulomb force is generated in the electrode composite, which is attracted to the collector as the counter electrode and is coated, thereby forming an electrode active material layer. In addition, as a calendering film, for example, a self-supporting film (self-assembled film) of an electrode active material layer stacked on the collector is considered, but it is not limited to this situation.
[0094] Substrate
[0095] The material used for the substrate is not particularly limited, and any material that can be used as a negative electrode collector of a battery can be appropriately used, such as copper, copper alloy, stainless steel (SUS), nickel, and products obtained by plating, coating, or vapor-depositing nickel, chromium, and carbon on these metals, but the present invention is not limited thereto.
[0096] The present disclosure will be described in more detail with reference to the following examples, but the scope of the present disclosure is not limited to these examples.
[0097] Example 1
[0098] Preparation of negative electrode active material layer A1
[0099] Graphite (particle size 20 μm) (95.0 parts by mass) as a negative electrode active material and polyvinylidene fluoride (PVdF) (particle size 150 nm) (5.0 parts by mass) as a binder were put into an MP mixer (multi-purpose small mixing pulverizer). Then, a composite treatment was carried out at a rotation speed of 10,000 rpm for 2 minutes to obtain a negative electrode composite. Secondly, the obtained negative electrode composite was formed on a Cu foil (8 μm) as a negative electrode collector using an electrostatic screen film forming method at a voltage of 0.5 kV and a distance of 1 cm between the collector foil and the screen. Then, the two sides of the negative electrode composite formed on the Cu foil were clamped by a flat plate heated at 160°C and pressurized for 1 minute with a load of 5 tons. Thus, a negative electrode active material layer A1 in which the negative electrode composite is fixed to the Cu foil was obtained.
[0100] Coverage rate of negative electrode active material layer A1
[0101] The side of the negative electrode active material layer A1 was observed by SEM, and the fluorine atoms contained only in the PVdF as a binder were mapped using EDX. Next, the binder area was calculated by binary conversion of the obtained image. The binder coverage was calculated based on the binder area relative to the particle area. The binder coverage of the negative electrode active material layer A1 was 10.1%.
[0102] Preparation of positive electrode active material layer B1
[0103] Nickel·cobalt·manganese oxide (NCM) as a positive electrode active material, acetylene black as a conductive aid, PVdF as a binder, and an appropriate amount of NMP as a dispersion medium are mixed to prepare a positive electrode composite slurry. The particle size of nickel·cobalt·manganese oxide (NCM) is 3 to 10 μm. 97.5 parts by mass of nickel·cobalt·manganese oxide (NCM) are used. 1.5 parts by mass of acetylene black are used. 1.0 parts by mass of PVdF are used. The obtained positive electrode composite slurry is applied on Al foil (12 μm) as a positive electrode collector and dried to make a positive electrode active material layer B1 on the positive electrode collector.
[0104] Production of Battery C1
[0105] The negative electrode active material layer A1 and the positive electrode active material layer B1 were placed opposite to each other via a separator and housed in a container. Next, 1.14 M LiPF6 / ethylene carbonate (EC): dimethyl carbonate (DMC): ethyl methyl carbonate (EMC) (30:34:36 volume %) was injected into the container as an electrolyte, and the container was sealed to produce a battery C1.
[0106] Battery capacity of battery C1
[0107] Battery C1 was discharged under constant current and constant voltage conditions (current 0.3C, voltage 4.25V to 2.5V, cut-off current 1 / 20C), and the discharge capacity was calculated. The discharge capacity of battery C1 was 190 mAh / g.
[0108] Reaction resistance of battery C1
[0109] The SOC (State of Charge) of the battery C1 was adjusted to 50%. Next, the AC impedance of the battery C1 was measured, and the reaction resistance was calculated from the Cole-Cole plot. The reaction resistance of the battery C1 was 0.33Ω.
[0110] Example 2
[0111] Preparation of negative electrode active material layer A2
[0112] A negative electrode active material layer A2 fixed to a Cu foil was prepared in the same manner as in Example 1 except that graphite (particle size 20 μm) (92.5 parts by mass) was used as the negative electrode active material and PVdF (particle size 150 nm) (7.5 parts by mass) was used as the binder. The binder coverage of the negative electrode active material layer A2 was 20.0%.
[0113] Production of Battery C2
[0114] Battery C2 was produced in the same manner as in "Production of Battery C1" of Example 1 except that negative electrode active material layer A2 was used instead of negative electrode active material layer A1. The battery capacity and reaction resistance of Battery C2 are shown in Table 1 below.
[0115] Comparative Example 1
[0116] Preparation of negative electrode active material layer a1
[0117] The negative electrode active material layer a1 fixed to the Cu foil was prepared by the same method as in "Preparation of negative electrode active material layer A1" of Example 1, except that graphite (particle size 20 μm) (97.5 parts by mass) was used as the negative electrode active material and PVdF (particle size 150 nm) (2.5 parts by mass) was used as the binder. The binder coverage of the electrode active material layer a1 was 4.0%.
[0118] Production of battery c1
[0119] Battery c1 was produced in the same manner as in "Production of Battery C1" of Example 1 except that negative electrode active material layer a1 was used instead of negative electrode active material layer A1. The battery capacity and reaction resistance of battery c1 are shown in Table 1 below.
[0120] Comparative Example 2
[0121] Preparation of negative electrode active material layer a2
[0122] A negative electrode active material layer a2 fixed to a Cu foil was prepared by the same method as in "Preparation of negative electrode active material layer A1" of Example 1, except that graphite (particle size 20 μm) (90.0 parts by mass) was used as the negative electrode active material and PVdF (particle size 150 nm) (10.0 parts by mass) was used as the binder. The binder coverage of the electrode active material layer a2 was 28.0%.
[0123] Production of battery c2
[0124] Battery c2 was produced in the same manner as in "Production of Battery C1" of Example 1 except that negative electrode active material layer a2 was used instead of negative electrode active material layer A1. The battery capacity and reaction resistance of battery c2 are shown in Table 1 below.
[0125] Table 1
[0126]
[0127] Batteries were fabricated using negative electrode active material layers with different amounts of binder produced by a dry process and positive electrode active material layers produced from a positive electrode composite slurry, and the discharge capacity and reaction resistance were evaluated.
[0128] Battery C1 including negative electrode active material layer A1 with a binder content of 5.0% and battery C2 including negative electrode active material layer A2 with a binder content of 7.5% were batteries with low reaction resistance and high discharge capacity (Examples 1 and 2).
[0129] However, the battery c1 including the negative electrode active material layer a1 with a binder content of 2.5% has a low reaction resistance but a low discharge capacity (Comparative Example 1). It is believed that when the amount of binder is small and the coverage of the negative electrode active material by the binder is small, SEI is formed on the surface of graphite, the irreversible capacity increases, and thus the discharge capacity decreases.
[0130] In addition, the battery c2 containing the negative electrode active material layer a2 with a binder content of 10.0% has a high discharge capacity but a high resistance (Comparative Example 2). It is believed that when the amount of binder is large and the coverage of the negative electrode active material by the binder is large, the conduction of lithium ions is hindered by the binder, thereby increasing the reaction resistance.
[0131] The above describes the preferred embodiments of the negative electrode active material layer, the method for producing the negative electrode active material layer, and the battery of the present disclosure, but those skilled in the art will appreciate that changes may be made without departing from the scope of the patent claims.
Claims
1. A negative electrode active material layer for a battery, wherein: The negative electrode active material layer includes a carbon-based negative electrode active material and a binder that covers the carbon-based negative electrode active material. The content of the binder is 4.0 to 9.0 mass % relative to the total amount of the negative electrode active material layer, and the coverage of the negative electrode active material by the binder is 8.0 to 25%.
2. The negative electrode active material layer according to claim 1, wherein The content of the binder is 6.0 to 9.0 mass % relative to the total amount of the negative electrode active material layer.
3. The negative electrode active material layer according to claim 1, wherein The content of the binder is 7.0 to 8.0 mass % relative to the total amount of the negative electrode active material layer.
4. The negative electrode active material layer according to claim 1, wherein The adhesive is polyvinylidene fluoride. 5 . A battery comprising the negative electrode active material layer according to claim 1 .
6. The method for producing a negative electrode active material layer according to any one of claims 1 to 4, comprising: Mixing a carbon-based negative electrode active material and a binder in an amount of 4.0 to 9.0 mass % relative to the total amount of the negative electrode active material layer to prepare a negative electrode composite; and The negative electrode composite material is coated on a substrate by a dry method to form the negative electrode active material layer.
7. The manufacturing method according to claim 6, wherein: The dry method is electrostatic painting.
8. The manufacturing method according to claim 6, wherein: The average particle size of the carbon-based negative electrode active material is 5 to 30 μm, and the average particle size of the binder is 100 to 500 nm.
Citation Information
Patent Citations
Electrode manufacturing method and electrode manufacturing device
JP2023016208A